GENOTYPING OF DRUG-RESISTANT MYCOBACTERIUM TUBERCULOSIS ISOLATES FROM SOUTHERN KAZAKHSTAN - Tarlykov , P.; Atavliyeva , S.; Alenova , A.; Zholdybayeva , E.; Ramankulov , Ye. (Eurasian Journal of Applied Biotechnology, 2019)
The incidence of drug-resistant tuberculosis in Kazakhstan has risen over the last decades, making it a serious threat. The purpose of this study was to characterize M. tuberculosis isolates circulating in the south of Kazakhstan, based on mutations of known association with multidrug-resistance and extensive drug resistance. A total of 58 clinical isolates of M. tuberculosis with drug resistance from southern Kazakhstan were selected. Seven genetic loci were sequenced, namely, rpoB (for resistance to RIF), katG, inhA (for resistance to INH), embB (for resistance to EMB), as well as the gyrA, gyrB (for resistance to CIP and OFX) and rrs (for resistance to KAN, AMK, and CPR). In addition, mutations in codon 315 of katG (n = 53; 91.4%), in codon 531 of the rpoB (n = 45; 77.6%), at the position of 1401 A/G of rrs (n = 33; 56.9%) and in the codon 94 of the gyrA were found to be prevalent in the samples. MIRU-VNTR typing showed that most isolates belong to the Beijing family (n = 53; 94.4%). Whole genome sequencing of a single M. tuberculosis strain from southern Kazakhstan was conducted. The emergence of drug-resistance is characteristic of the Beijing family, which may explain the increase in the incidence rates of resistant forms of tuberculosis in Kazakhstan.